차전초의 에탄올추출물이 3T3-L1 지방세포의 지방축적 및 지질대사에 미치는 영향 - 전서영; Seo Young Jeon; 박지영; Ji Young Park; 신인순; In Soon Shin; 김성옥; Sung Ok Kim; 안희덕; Hee Duk An; 김미려; Mi Ryeo Kim (大韓本草學會誌, 2014)
The effects of ethanol extract of Plantago asiatica L. were investgated on adipocyte differentiation, lipopogenesis, lipolysis and apoptosis using differnentiated 3T3-L1 adipocytes.Methods : Plantago asiatica L. was extracted with ethanol (CCE). We carried on MTT assay for cell proliferation, Oil Red O staining for determination of cell differentiation and intracelluar adipogenesis. TUNEL staining assay for cell apoptosis, and Western blot analysis for measurement of pAMPK and pACC, C/EBPα, PPARγ protein expressions were performed. Results : The addition of CCE up to 0.2 mg/ml into cell culture media showed no cytotoxicity. Treatment of 0.2 mg/ml CCE significantly inhibited differentiation in 3T3-L1 preadipocytes. Lipid accumulation of the CCE treated cells was decreased compared with that of control. Induction of cell apoptosis was increased in CCE treated cells compared with that of control. AMPK and ACC levels of the cells with 0.2 mg/ml CCE were led to phosphorylation and also expressions of C/EBPα and PPARγ, as adipogenic transcription factors, were suppressed compared with those of control. Conclusions : Taken together, these results provide evidence that CCE has a regulatory role in lipid metabolism that is related to differentiation into adipocytes, adipogenesis and apoptosis.